Fenomena Hari Tanpa Bayangan Sebagai Penanda Awal Waktu Salat Dzuhur di Kabupaten Enrekang - Andi Mulia Amelia; irfan; Imam Permana (Universitas Islam Negeri Alauddin Makassar, 2023)
This study aims at 1) to find out the stages of the process do not appear to be solar shadows in a shadowless phenomenon of days, 2) to learn of a shadowless phenomenon in verifying the beginning of the time when the Dzuhur sciene perspective. this type of research is